Assessment of Knowledge about Immunization among Mothers of Under Five Children Attending Immunization in Tertiary Care Hospital in Udaipur - Reshma Reja; Rekha Bhatnager; Atul Kumar Gupta (Medsci Publications, 2018)
Background: Immunization is one of the most effective, safest and efficient Public Health Intervention. While the impact of Immuni- zation on childhood morbidity & mortality has been great, it's full potential has yet to be reached. The knowledge of mothers is an important factor for better immunization coverage. Methodology:A hospital based cross sectional study with pre- designed semi structured questionnaire was done among mothers of under five children attending the immunization center at RNT medical college, Udaipur. The sample comprised of 320 mothers. Results: 98.4% mothers knew that immunization is beneficial for their children. 37.2% were aware about the side effects of vaccines. 69.2% mothers acquired knowledge regarding immunization from antenatal clinics. 28% mothers have good knowledge about im- munization. Conclusion: Ample health education should be given to mothers residing in rural areas to raise their knowledge regarding immun- ization. In rural areas Anganwadi workers, ASHA etc should play a significant role in bringing awareness about vaccinations and their benefits.